2000
DOI: 10.1002/1521-396x(200006)179:2<403::aid-pssa403>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Hole-Filling above Tc, at the Origin of the In-Plane Resistivity Anomaly in Bi-2212 Crystals

Abstract: We have observed a sharp peak (100%) in the in-plane resistivity r ab just above T c , in Bi-2212 crystals, in agreement with previous results from Han et al. who attributed this anomaly to the ªquasi-reentrant behaviourº already observed for polycrystalline samples. This explanation is very likely unadapted to these crystals and we propose another one related to a model we had used to fit r c T curves for Bi-2212 underdoped crystals, namely, an increase of the Fermi level (hole-filling) with decreasing temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The increase of the coupling energy, with decreasing temperature, should be due to a hardening with decreasing temperature of the Cu-O bonding inside the CuO 2 planes. Such a hardening in the Cu-O bond with temperature can explain simultaneously (i) the anomalous dilatation and lattice parameter variations with temperature and (ii) the anomalous resistivity variation observed in the a-b plane as well as along c. In the latter case the increase of the Fermi level, previously suggested [6,11] to be at the origin of these resistivity anomalies, can be directly related to the change in the Cu-O bonding. For similar reasons a 'phase transition in the Cu-O ligands' was recently suggested to occur, by Owens [27], in cuprates with ladder-like structure.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The increase of the coupling energy, with decreasing temperature, should be due to a hardening with decreasing temperature of the Cu-O bonding inside the CuO 2 planes. Such a hardening in the Cu-O bond with temperature can explain simultaneously (i) the anomalous dilatation and lattice parameter variations with temperature and (ii) the anomalous resistivity variation observed in the a-b plane as well as along c. In the latter case the increase of the Fermi level, previously suggested [6,11] to be at the origin of these resistivity anomalies, can be directly related to the change in the Cu-O bonding. For similar reasons a 'phase transition in the Cu-O ligands' was recently suggested to occur, by Owens [27], in cuprates with ladder-like structure.…”
Section: Discussionmentioning
confidence: 73%
“…On the basis of these measurements, and no structural change being observed in this temperature range, several authors have suggested a change either in the Cu-O or in the Bi-O bonds [1,2,6,11] to explain the existence of these anomalies, that can give rise to a 'hole filling' with decreasing temperature. Some other, very different, kinds of explanation have also been given.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation